Preparation and Characterization of Microcapsules Containing Antioxidant Fish Protein Hydrolysates: a New Use of Bycatch in Brazil - Camargo, Tavani Rocha [UNESP]; Khelissa, Simon; Chihib, Nour Eddine; Dumas, Emilie; Wang, Jian; Valenti, Wagner C. [UNESP]; Gharsallaoui, Adem (Springer Nature, 2021)
In this study, we evaluated the effect of complexation and microencapsulation with pea protein on the antioxidant activity of protein hydrolysates from bycatch in Brazil. The zeta potential values of complexes changed from negative to positive with the increase of pea protein as a result of positively charged complexes formation. The increase in the ratio of pea protein/hydrolysates also resulted in increased turbidity in all samples. Particle size measurements indicated that the complexes tended to form larger aggregates (ranged from 61.5 ± 1.7 μm to 183 ± 2.8 μm). The 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity of the pea protein/fish protein hydrolysate complexes was higher than that of the protein hydrolysates alone. Moreover, increasing levels of pea protein did not affect the antioxidant activity of fish protein hydrolysates. The complexes of the Paralonchurus brasiliensis were chosen for the microencapsulation process by spray-drying. The results revealed that spray-drying did not have a significant effect (P > 0.05) on the protein hydrolysate antioxidant activity when they were complexed with pea protein. Thus, this work suggests that the complexation with pea protein and subsequent microencapsulation by spray-drying is an efficient way to protect the biological activity of protein hydrolysates obtained from bycatch. This study provides evidence for the potential use of bycatch from shrimp fisheries as functional ingredients or nutraceuticals.
Keywords: DPPH; Microencapsulation; Micropogonias furnieri; Paralonchurus brasiliensis; Pea protein